Can ecological restoration improve soil properties and plant growth in valley-slope sand dunes on southern Tibetan Plateau?. (4th March 2021) - Liao, Chengrui; Li, Haidong; Lv, Guoping; Tian, Jiarong; Liu, Bo; Tian, Meirong; You, Guangyong; Xu, Yannan
ABSTRACT: Global warming poses a serious threat to the alpine grassland on the Tibetan Plateau. Ecological restoration is an effective measure for adapting to climate change and controlling desertification. However, few studies have focused on the relationship between plant growth and the soil properties of valley-slope sand dunes during ecological restoration. We conducted a case study to investigate the changes in the soil properties at various elevations during two stages of ecological restoration. Our results indicated improvements in the plant growth and soil quality during the ecological restoration from 2011 to 2017. The soil particle size changed from predominantly medium-fine sand at stage 1 (2011) to very fine sand at stage 2 (2017). The soil organic matter and total N content ranged from 1.04–1.10 g·kg −1 and 0.06–0.07 g·kg −1 at different elevations in stage 1 and increased to 12.30–14.75 g·kg −1 and 2.82–3.08 g·kg −1, respectively, in stage 2. Higher plants were distributed mainly in the midslope area at stage 2. A significant positive correlation was observed between pH and plant height at stage 2. These findings improve our understanding of the changes in soils and plants on sandy land and their relationships during ecological restoration of alpine valleys.